STUDENTS’ METAPHORICAL THINKING SKILLS IN STATISTIC METHOD SUBJECT DURING COVID-19 PANDEMIC - I Putu Ade Andre Payadnya; Kadek Adi Wibawa (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study was to analyze students' metaphorical thinking skills in the statistic method subject during COVID-19 Pandemic using three stages of metaphorical thinking. This research was conducted from March to May 2020. Subjects in this study were 11 students of class IIB of Mathematics Education Study Program Mahasaraswati University Denpasar. This study uses descriptive analysis techniques. Data collected through tests, interviews, observations, and documentation. The results showed that students’ metaphorical thinking skills in online learning during COVID-19 Pandemic was still very low where only 20% of students answered correctly at the grounding metaphors stage, 25% at the linking metaphors stage, and only 25% at the redefinitional metaphors stage. Students tend to be confused when required to associate statistical concepts with everyday phenomena and discover the characteristics of the concepts. Online learning due to COVID-19 Pandemic also causes the suit of students to do group discussion as well as the decrease in student motivation primarily in solving metaphorical thinking questions. Some solutions that can be taken to overcome this problem are: 1) Using interactive learning, 2) Using Project-Based learning (PBL), 3) Discussing current trends in learning, 4) Demonstrating assertiveness, and establishing learning rules.